2008
DOI: 10.1159/000147467
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Activity during the Digit Symbol Substitution Test Determined by Multichannel Near-Infrared Spectroscopy

Abstract: Backgrounds: The digit symbol substitution test (DSST) is a clinically useful and widely accepted tool for the detection of various psychiatric disorders. Investigating neural activity during the DSST is useful when considering the relationship between the poor performance on the DSST and neurocognitive deficits. However, obtaining reliable functional imaging of the neural mechanisms associated with this test is challenging due to motion artifacts. Aims: To circumvent this problem, we examined frontal lobe act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 67 publications
4
26
0
Order By: Relevance
“…Visuospatial perception, selective attention, response speed, visuomotor coordination and incidental memory of the association of digit symbol pairs may play a role in digit symbol substitution test performances. It is also considered to reflect executive processing, which is consistent with the frontal activity recently demonstrated during its execution [75] . The multicomposite qualities of the DSST are confirmed in our study by its significant correlations with all cognitive measures, and, more specifically, by the significant correlations ranging from 0.50 to 0.62 with the cognitive measures associated with the 3 unsafe indicators taken in isolation.…”
Section: Discussionsupporting
confidence: 79%
“…Visuospatial perception, selective attention, response speed, visuomotor coordination and incidental memory of the association of digit symbol pairs may play a role in digit symbol substitution test performances. It is also considered to reflect executive processing, which is consistent with the frontal activity recently demonstrated during its execution [75] . The multicomposite qualities of the DSST are confirmed in our study by its significant correlations with all cognitive measures, and, more specifically, by the significant correlations ranging from 0.50 to 0.62 with the cognitive measures associated with the 3 unsafe indicators taken in isolation.…”
Section: Discussionsupporting
confidence: 79%
“…The DSST, a component of the Wechsler Adult Intelligence Test and a test of visuospatial and motor speed-of-processing, has a considerable executive function component and is frequently used as a sensitive measure of frontal lobe executive functions [17]. The DSST was used to assess participant cognitive function tasks of pairing (each digit, 1–9, has a symbol it is associated with) and information processing.…”
Section: Methodsmentioning
confidence: 99%
“…The Digit Symbol subtest is part of the processing speed factor of the WAIS-R and has been interpreted as a measure of executive function in the research literature [34][35][36][37][38][39][40] in part because of its requirements for shifting of attention (i.e., alternating from digit string to symbol key), holding and manipulation of information in working memory (i.e., the key of digits and corresponding symbols), and inhibition of inappropriate responses (i.e., copying the digit rather than it's corresponding symbol). A recent study by Nakahachi and colleagues using near infra-red spectroscopy [41] demonstrated that performance of the Digit Symbol test activated areas of the cortex known to be associated with executive functions [42].…”
Section: Digit Symbolmentioning
confidence: 99%